Before learning the product rule of logarithms, we have to be aware of the parts of a logarithm.
Consider the logarithm given below.
logba
In the logarithm above, 'a' is called argument and 'b' is called base.
Logarithm of product of two numbers is equal to the sum of the logarithms of the numbers to the same base.
logamn = logam + logan
In other words, we can simplify the addition of two logarithms, if the they have the same base. That is, if two logarithms with same base are in addition, we can write single logarithm with the given base and the argument is the product of two arguments.
logxa + logxb = logxab
Apart from the product rule of logarithms, there are two other important rules of logarithm.
(i) Quotient Rule
(ii) Power Rule
Logarithm of the quotient of two numbers is equal to the difference of their logarithms to the same base.
loga(m/n) = logam - logan
Logarithm of a number raised to a power is equal to the power multiplied by the logarithm of the number to the same base.
logamn = nlogam
Problem 1 :
Find the logarithm of 125 to the base 5.
Solution :
Write 125 as a power of 5.
125 = 5 x 5 x 5
= 53
log5125 = log5(5)3
= 3log55
= 3(1)
= 3
Problem 2 :
Find the logarithm 1728 to the base 2√3.
Solution :
Write 1728 as a power of 2√3.
1728 = 2 x 2 x 2 x 2 x 2 x 2 x 3 x 3 x 3
1728 = 26 x 33
1728 = 26 x [(√3)2]3
1728 = 26 x (√3)6
1728 = (2√3)6
log2√3(1728) = log2√3(2√3)6
Using the power rule of logarithms,
= 6log2√3(2√3)
= 6(1)
= 6
Problem 3 :
Find the logarithm of 0.001 to the base 0.1.
Solution :
log0.10.001 = log0.1(0.1)3
= 3log0.10.1
= 3(1)
= 3
Problem 4 :
Find the logarithm 1/64 to the base 4.
Solution :
log4(1/64) = log41 - log464
= 0 - log4(4)3
= -3log44
= -3(1)
= -3
Problem 5 :
Find the logarithm of 0.3333...... to the base 3.
Solution :
log3(0.3333......) = log3(1/3)
= log31 - log33
= 0 - 1
= -1
Problem 6 :
If logy(√2) = 1/4, find the value of y.
Write the equation in exponential form.
√2 = y1/4
Raise to the power 4 on both sides.
(√2)4 = (y1/4)4
(21/2)4 = y
22 = y
4 = y
Problem 7 :
Simplify :
(1/2)log1025 - 2log103 + log1018
Solution :
= (1/2)log1025 - 2log103 + log1018
Using power rule of logarithms,
= log10251/2 - log1032 + log1018
= log10(52)1/2 - log1032 + log1018
= log105 - log109 + log1018
= log105 + log1018 - log109
Using the product rule of logarithms,
= log10(5 x 18) - log109
= log1090 - log109
Using the quotient rule of logarithms,
= log10(90/9)
= log1010
= 1
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 10, 25 06:02 PM
Feb 10, 25 07:03 AM
Feb 10, 25 07:01 AM